71. Cerebellum modulates defensive response within the peripersonal space. Issue 12 (December 2016) - Barloscio, D.; Parenti, L.; Bartolotta, M.; Vergari, M.; Ferrucci, R.; Priori, A.; Santarcangelo, E.; Di Rollo, A.; Carli, G.; Sartucci, F.; Bocci, T.
Abstract : We evaluated the role of cerebellum in defensive responses, by recording the Hand Blink Reflex (HBR) and modulating cerebellar activity with transcranial Direct Current Stimulation (tDCS). The active electrode was centered on the median line 2 cm below the inion and the return one over the right shoulder. Direct current was applied for 20 min with an intensity of 1.5 mA, both for cathodal and anodal stimulation. For the recording of HBR, we stimulated electrically the median nerve at the wrist and recorded EMG activity from the orbicularis oculi muscle bilaterally. Depending on the hand position respective to the face, we assessed four different conditions: "hand-far", "hand-near" (eyes-open), "hand-side", "hand-near" (eyes-closed). EMG signals were high-pass filtered (55 Hz), full-wave rectified, and averaged separately for the four conditions at the ipsilateral and contralateral recording sides. The anodal stimulation reduces the magnitude of the HBR, as measured by the Area Under the Curve (AUC), and increased the HBR latency in the "hand-side" and "hand-near" (eyes-closed) conditions (HBR magnitude: p  = 0.004 and p  < 0.0001; HBR latency: p  = 0.023 and 0.002, respectively). These results support a critical role of the cerebellum in the defensive responses within the peripersonal space, thus selectively modulating defensive behavior when the visual feedback is missing.